The Influence of Praying and Surrendering to God on The Level of Test Anxiety in Students - Hidayatulloh, Ahmad; Hakim, Siti Nurina (Universitas Muhammadiyah Surakarta, 2025)
The phenomenon of exam anxiety in students is a serious problem that can have an impact on academic performance. This study was designed to empirically examine the effect of praying and surrendering on students' anxiety in facing exams. This research method uses a descriptive quantitative approach. The research hypothesis is that there is an influence between prayer and surrender on the level of exam anxiety in students. The population of this study was UMS Psychology students amounting to 319 people, with a sample of 80 students taken using purposive sampling technique. Data collection using test anxiety scale, prayer scale, and surrender scale. Using multiple linear regression analysis, results showed a significance value of 0.000 (p<0.01) and R² = 0.324, which means that praying and surrendering simultaneously have a very significant influence on exam anxiety in students with a contribution of 32.4%. Praying and surrendering with sincerity are closely related to psychological health, so it can reduce anxiety.